Chess in the Middle Ages and Early Modern Age : a Fundamental Thought Paradigm of the Premodern World. - O'Sullivan, Daniel E. (Fundamentals of medieval and early modern culture., 2012)
More than a mere pastime, chess was an important pedagogical tool and thought paradigm in the Middle Ages. Much like people today who speak in sports metaphors, the people of medieval Europe related life to chess, making comparisons on and off the board to war, politics, love, and the social order. In this collection of essays, scholars investigate chess texts from various European traditions and make the case for seeing chess as an important key to understanding medieval culture.